2021
DOI: 10.3390/ijms22094373
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Alleviates the Inhibitory Effect of Tunicamycin-Induced Endoplasmic Reticulum Stress on Expression of Genes Involved in Thyroid Hormone Synthesis in FRTL-5 Thyrocytes

Abstract: Recently, ER stress induced by tunicamycin (TM) was reported to inhibit the expression of key genes involved in thyroid hormone synthesis, such as sodium/iodide symporter (NIS), thyroid peroxidase (TPO) and thyroglobulin (TG), and their regulators such as thyrotropin receptor (TSHR), thyroid transcription factor-1 (TTF-1), thyroid transcription factor-2 (TTF-2) and paired box gene 8 (PAX-8), in FRTL-5 thyrocytes. The present study tested the hypothesis that resveratrol (RSV) alleviates this effect of TM in FRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Cellular stress [ 22 ] was abolished by treatment of antithyroid drug. Resveratrol (RSV) alleviates tunicamycin (TM)-induced ER stress by attenuating expression of genes involved in thyroid hormone synthesis in FRTL-5 thyrocytes [ 23 ]. Yuan Lili found that the HAMA scores in the thyrotoxic group were significantly higher than those in the subclinical thyrotoxic group and subclinical hypothyroidism group ( p =0.042; p =0.025); HAMA scores were significantly positively related to T3 and T4 ( r = 0.158, p =0.040; r = 0.169, p =0.028) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular stress [ 22 ] was abolished by treatment of antithyroid drug. Resveratrol (RSV) alleviates tunicamycin (TM)-induced ER stress by attenuating expression of genes involved in thyroid hormone synthesis in FRTL-5 thyrocytes [ 23 ]. Yuan Lili found that the HAMA scores in the thyrotoxic group were significantly higher than those in the subclinical thyrotoxic group and subclinical hypothyroidism group ( p =0.042; p =0.025); HAMA scores were significantly positively related to T3 and T4 ( r = 0.158, p =0.040; r = 0.169, p =0.028) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTF-1 is critically involved in the transcriptional regulation of the expression of key thyroid hormone synthesis-related molecules. 28 Due to the relatively small sample size, the relationship between changes in TG levels and the progression to OH did not reach statistical significance, but there was still a correlation trend between them. Therefore, we cannot absolutely conclude that the changes in TG levels were completely unrelated to the progression to OH.…”
Section: Discussionmentioning
confidence: 96%
“…TTF-1 is critically involved in the transcriptional regulation of the expression of key thyroid hormone synthesis-related molecules. 28 …”
Section: Discussionmentioning
confidence: 99%
“…( 23 ) demonstrated that PA could suppress NIS, TPO, and Tg mRNA levels, as well as promote intracellular lipid accumulation. Several studies have illustrated that endoplasmic reticulum (ER) stress could inhibit the expression of the three key molecules and their regulators in the thyrocytes ( 41 , 42 ). In addition, ER stress was also observed in HFD rats and PA-treated thyrocytes, along with the increased degradation rate of Tg, which further indicated that the effect of ER stress on HFD-induced hypothyroidism might contribute to a decrease in the production of Tg ( 35 ).…”
Section: Discussionmentioning
confidence: 99%